HUBUNGAN PENGETAHUAN IBU DENGAN KEPATUHAN PEMBERIAN IMUNISASI CAMPAK PADA BALITA DI WILAYAH KERJA PUSKESMAS KOTA MANNA BENGKULU SELATAN - Hanifah Hanifah; Yozi Martiani (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
Measles is one of the infectious diseases that causes death in infants due to its compilation. To prevent this, the vaccination program occupies a very important role. This research aims to determine the relationship between mother’s knowledge and obedient with measles immunization at The Primary Health Working Area, Manna City, South Bengkulu. The type of this research is quantitative using cross sectional design. The population in this study were all mothers who have children aged > 11 months who visited to Primary Health Care, Manna City, South Bengkulu, as many as 146 persons. The sampling technique in this research used Accidental Sampling technique that are as many as 59 persons. The data analysis used Chi-Square statistical test and obtained the value of ρ - Value = 0.016. The result of the Contingency Coefficient test was obtained the value of C = 0.351 with a less category. It was concluded that there was a significant relationship between mother’s knowledge and obedient with measles immunization at The Primary Health Working Area, Manna City, South Bengkulu.with less category. It is expected that mothers able to increase knowledge about measles immunization in an effort to reduce the infant mortality rates. Keywords : Knowledge, Compliance With Measles Immunization